Pharmacological Manipulation of Kv7 Channels as a New Therapeutic Tool for Multiple Brain Disorders - Vigil, Fabio A.; Carver, Chase M.; Shapiro, Mark S. (Frontiers in Physiology, 2020)
Kv7 (”M-type,” KCNQ) K+ currents, play dominant roles in controlling neuronal excitability. It acts as a “brake” against hyperexcitable states in the central and peripheral nervous systems. Pharmacological augmentation of M current has been developed for controlling epileptic seizures, although current pharmacological tools are uneven in practical usefulness. Lately, however, M-current “opener” compounds have been suggested to be efficacious in preventing brain damage after multiple types of insults/diseases, such as stroke, traumatic brain injury, drug addiction and mood disorder. In this review, we will discuss what is known to date on these efforts and identify gaps in our knowledge regarding the link between M current and therapeutic potential in these disorders. We will outline the preclinical experiments that are yet to be performed to demonstrate the likelihood of the success of this approach in human trials. Finally, we also address multiple pharmacological tools available to manipulate different Kv7 subunits and the relevant evidence for translational application in the clinical use for disorders of the central nervous system and multiple types of brain insults. We feel there to be great potential for manipulation of Kv7 channels as a novel therapeutic mode of intervention in the clinic, and that the paucity of existing therapies obligates us to perform further research, so that patients can soon benefit from such therapeutic approaches.